(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article attempts to analyze the didactic aspect using information technologies, reveals their importance for the development and organization of independent work among future history teachers, analyzes the relevance in practice. The didactic properties of ICT, reflecting the information aspect, are briefly described, the main distinctive features of the didactic functions of ICT, the use of ICT in the framework of the personality-oriented and activity-based approaches are listed.